The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s10610-011-9155-x
|View full text |Cite
|
Sign up to set email alerts
|

Policing Public Drugs Nuisance Through The Anti-Social Behaviour Legislation: Questions and Contradictions

Abstract: This paper reports findings from a London-based study and provides evidence of rigorous law enforcement activity being enacted in drives to alleviate local areas of public drugs nuisance, namely the use of anti-social behaviour orders (ASBOs) and dispersal and banning orders, as well as the closure of 'crack houses'. The paper acknowledges these legislative tools were necessary to deal with the real life problems of visible drugs nuisance that had grown up in some communities, but it draws attention to the way… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…As an example of this, Sanders (2005) has described how club security staff often display a 'blind-eye' attitude or are even complicit in the selling and use of drugs (see also Hobbs et al, 2003). Complementing these findings, Ward (2011) argues that, contrary to the hard-line approaches used to target visible hard-end drug users in public spaces in London, recreational drug use hidden within the private domains of bars and nightclubs has generated little public debate and police attention.…”
Section: Concluding Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example of this, Sanders (2005) has described how club security staff often display a 'blind-eye' attitude or are even complicit in the selling and use of drugs (see also Hobbs et al, 2003). Complementing these findings, Ward (2011) argues that, contrary to the hard-line approaches used to target visible hard-end drug users in public spaces in London, recreational drug use hidden within the private domains of bars and nightclubs has generated little public debate and police attention.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…While existing research has suggested that the cultural normalization of clubbers' drug use (Duff, 2005) has been coupled with a relative relaxation in the regulation of drug activities inside venues (Sanders, 2005;Ward, 2011), this article challenges such assumptions by arguing for the need for more nuanced understandings of drug policing in nightlife spaces. The article points to a growing governmental intolerance of drugs in Danish nightlife spaces, and analyses how drug-using clubbers are targets of inter-related police and club security banning measures aimed at excluding them from entire nightlife districts.…”
Section: Introductionmentioning
confidence: 86%